Rapid PCR-RFLP Screening of CYP21A2 Variants: Bridging Molecular Diagnostics in a Low-Resource Setting - Larasati, Irene Astrid; Maharani, Nani; Utari, Agustini; Winarni, Tri Indah (Faculty of Medicine, Universitas Diponegoro, 2026)
Background: The 21-hydroxylase deficiency (21OHD) accounted for the majority of autosomal recessive inherited congenital adrenal hyperplasia (CAH) cases. A genetic test could offer a more thorough diagnostic approach because of the wide range of disease’s severity, but it was challenging in a resource-limited setting.Objective: To apply a simple and cost-effective rapid molecular screening for detecting the most common CYP21A2 variants causing salt-wasting (SW) CAH.Methods: DNA extraction was conducted using a salting out method from a venous blood sample taken from 49 CAH patients without prior genetic testing. A PCR-RFLP approach was utilized using primer sets specifically designed to anneal to the CYP21A2. Specific restriction enzymes were selected to cleave the DNA sequence, differentiating the wild and mutant type, i.e, the p.Arg357Trp, p.Gln318Ter, IVS2-13A/C>G, and exon 6 cluster. Samples positive for those mutation types detected from DNA sequencing, used as positive controls.Results: The most common variant was IVS2-13A/C>G, detected in 26 out of 27 patients. Only 6.1% of 49 patients were found to have the p.Gln318Ter variant. Both the p.Arg357Trp and exon 6 cluster carried inconclusive results. All patients detected with the IVS2-13A/C>G and p.Gln318Ter had a phenotype of SW CAH.Conclusion: The PCR-RFLP was an advantageous method for identifying CYP21A2 variants in a low-resource setting. Nevertheless, the use of multiplex ligation-probe dependent amplification (MLPA) and Sanger sequencing offered a comprehensive analysis to discover novel variants that could help with patients' diagnosis and treatment.